PERAN INTELLEGENCE QUOTIENT (IQ), EMOSIONAL QUOTIENT (EQ) DAN SPIRITUAL QUOTIENT (SQ) DALAM PENINGKATAN MUTU PENDIDIKAN - Irawan, Andik Rony (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2005)
Human being is the best and excellent creature. Human does not only have potency of rational intelligence but also emotional and spiritual intelligence. In fact, the emotional and spiritual intelligence are so central in someone achievement. Cause, the level of those two intelligences is on top of rational intelligence. Nevertheless, these two matters is not yet studied and developed comprehensively.In consequence, to increase quality of education forwards, institute of education has to able to develop potencies of those two intelligences, not merely rational intelligence.Keywords: IQ, EQ, SQ and Quality of Education